Analysis of wave scattering on piezoelectric surface with flexoelectric effect. (28th March 2022) - Mondal, Sonali; Sahu, Sanjeev A.; Nirwal, Sonal
Abstract : In this paper, a mathematical study is carried out to investigate the reflection phenomenon of plane QP waves at mechanically traction‐free and dielectrically charge‐free boundary surface of a pre‐stressed rotating piezoelectric half‐space. The microstructure effect (flexoelectric effect) is considered in the piezoelectric half‐space along with micro‐inertial effect as well as strain gradient effect. Due to the reflection phenomenon at the free surface, five kinds of coupled elastic waves are generated. The reflection coefficients are evaluated numerically. Graphs are plotted, and detailed discussion is presented to elaborate the effects of initial stresses, rotation, and flexoelectric coefficient on the reflection coefficients. It is observed that aforementioned parameters have remarkable influence upon the reflection coefficients of the reflected waves.